2019
DOI: 10.1155/2019/3410953
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bioactive Compounds and Analysis of Inhibitory Potential of the Digestive Enzymes fromSyzygiumsp. Extracts

Abstract: Diabetes and obesity represent major public health problems worldwide. High cost of medicines and drug treatments propose the research for less expensive alternatives, such as enzymatic inhibitors present in medicinal plants from natural sources. An example of such medicinal plant is the jambolan Syzygium sp., which is referred to be hypoglycemic and efficient in weight loss. With this in mind, we identified the bioactive compounds from Syzygium sp. commercial teas and evaluated the inhibitory potential and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In a clinical trial, Sahana et al (2010) [125] reported the effectiveness of S. cumini seed dosage by the oral route against diabetes (type 2) with no toxic effects on human subjects. Moreover, research findings supported the antidiabetic activity of S. cumini seeds due to the reduction of carbohydrate-hydrolyzing enzymes by the carotenoid luteolin, which binds at the αamylase site and acts as an inhibitor of carbohydrate breakdown similar to acarbose [126]. This mechanism of action and results aligned with previous research studies on antidiabetic potential conducted by Karthic et al (2008) [127] and Ponnusamy et al (2011) [128].…”
Section: Antidiabetic Potentialsupporting
confidence: 86%
“…In a clinical trial, Sahana et al (2010) [125] reported the effectiveness of S. cumini seed dosage by the oral route against diabetes (type 2) with no toxic effects on human subjects. Moreover, research findings supported the antidiabetic activity of S. cumini seeds due to the reduction of carbohydrate-hydrolyzing enzymes by the carotenoid luteolin, which binds at the αamylase site and acts as an inhibitor of carbohydrate breakdown similar to acarbose [126]. This mechanism of action and results aligned with previous research studies on antidiabetic potential conducted by Karthic et al (2008) [127] and Ponnusamy et al (2011) [128].…”
Section: Antidiabetic Potentialsupporting
confidence: 86%
“…For the understanding of receptor-binder interactions, the study of molecules employing molecular docking has become increasingly relevant to predict bond modes and elucidate experimental results [ 17 ]. Based on this, the molecular docking routines generated values of RMSD ( Root Mean Square Deviation) [ 18 ] and bond-free energy [ 19 ] for complexes formed with variations in RMSD values from 1060 to 1978 Å, and bond-free energy of −6.6 to −4.7 kcal/mol ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pancreatic α-amylase inhibition assay was carried out according to Freitas et al [ 19 ] with some modifications. The porcine pancreatic α-amylase (1 mg/mL) was incubated in 50 mM Tris-HCl buffer (pH 7.0) containing 10 mM CaCl 2 and 1% starch.…”
Section: Methodsmentioning
confidence: 99%